2019
DOI: 10.3390/agriculture9010013
|View full text |Cite
|
Sign up to set email alerts
|

Modified Over-the-Row Machine Harvesters to Improve Northern Highbush Blueberry Fresh Fruit Quality

Abstract: Improved blueberry mechanical harvesting (MH) equipment that maintains fresh market quality are needed due to rising costs and decreasing availability of laborers for harvesting by hand. In 2017, a modified over-the-row (OTR) blueberry harvester with experimental catch surfaces and plates designed to reduce fruit bruising was evaluated. The catch surfaces were made of neoprene (soft catch surface; SCS) or canvas (hard catch surface; HCS) and compared to hand-picked fruit (control). Early- and early/mid-season … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
1
13
1
Order By: Relevance
“…However, these SHB cultivars were firmer than NHB cultivars 'Legacy' and 'Liberty' (178 and 152 g/mm, respectively) [11]. In another study that harvested NHB cultivars with handheld shakers, 'Elliott' and 'Aurora' were also softer (155 and 172 g/mm, respectively) than the SHB cultivars in this study [16]. In these reports, there were minimal differences in bruising due to catch surface type.…”
Section: Discussioncontrasting
confidence: 54%
“…However, these SHB cultivars were firmer than NHB cultivars 'Legacy' and 'Liberty' (178 and 152 g/mm, respectively) [11]. In another study that harvested NHB cultivars with handheld shakers, 'Elliott' and 'Aurora' were also softer (155 and 172 g/mm, respectively) than the SHB cultivars in this study [16]. In these reports, there were minimal differences in bruising due to catch surface type.…”
Section: Discussioncontrasting
confidence: 54%
“…Brown, et al [22] showed that an experimental blackberry harvester reduced blueberry bruising 10% (from 77% to 68%) compared to commercial harvesters available at that time. Various researchers have reported that blueberry impact damage can be mediated by cushioning hard impact surfaces [5,6,[10][11][12]22]. The present study showed that, although bruise incidence was significantly higher in MH versus HH blueberries, retrofitting the OTR harvester with SCS reduced bruising severity by 30% to 60%, depending on the cultivar.…”
Section: Discussionmentioning
confidence: 40%
“…However, for both harvests, cultivar influenced packout (71% to 81%) more than catch surface. Studying NHB cultivars, DeVetter et al [12] found differences in packout between "Duke" (84%) and Draper (74%). In contrast, marketable packout was similar for SHB cultivars Meadowlark (88%) and Farthing (91%) [11], in which the decrease in packout was due to a higher percentage of unripe fruit being picked.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations